2018
DOI: 10.1021/acs.iecr.8b01943
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Distribution of Functional Groups in Semibatch Radical Copolymerization: An Accelerated Stochastic Approach

Abstract: While Kinetic Monte Carlo (KMC) techniques provide a powerful means to model polymer microstructure, the associated computational cost has been a barrier to their widespread adoption. The case of radical semibatch polymerization under starved-feed policy is a particularly challenging application: at the initial stage, a large simulation volume is required to accurately represent the low concentration of radicals generated at the start of the reaction, while the reactant feed dictates the further increase of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 34 publications
0
49
0
Order By: Relevance
“…Kinetic Monte Carlo ( k MC) modeling allows to track several molecular characteristics along the synthesis 16,18,19,3539 . In particular, k MC modeling allows to calculate the number of chains with a certain chain length (CL; equivalently the total number of monomer units) and a given number of functional comonomer units (FUNC value) so that in the context of the present work a bivariate functionality-chain length distribution (FUNC-CLD) can be constructed, with D highlighting the distributed nature of the variates in front 37,38 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kinetic Monte Carlo ( k MC) modeling allows to track several molecular characteristics along the synthesis 16,18,19,3539 . In particular, k MC modeling allows to calculate the number of chains with a certain chain length (CL; equivalently the total number of monomer units) and a given number of functional comonomer units (FUNC value) so that in the context of the present work a bivariate functionality-chain length distribution (FUNC-CLD) can be constructed, with D highlighting the distributed nature of the variates in front 37,38 .…”
Section: Resultsmentioning
confidence: 99%
“…Quality assessment is currently performed based on simplified reaction schemes and average functionalization degrees so that the distributed nature of the functional monomer incorporation is significantly wiped out. Chain-to-chain deviations can nonetheless be expected based on recent theoretical studies, with a distribution both in chain length (CL) and composition (e.g., the number of functionalities FUNC) 1419 . It is therefore crucial to develop a tool allowing to quantify the fraction of non-functionalized ( f nonfunctionalized ), single or even multiple functionalized chains for a broad range of functionalization chemistries.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the design challenges in synthesizing engineered materials, mathematical models and simulators are essential in bridging kinetic and process conditions to the resulting structures. We have recently shown that coupling the so-called scaling method [24,25] with a volume correction approach significantly decreases the computational time required for kinetic Monte Carlo (KMC) simulation, approaching that of the deterministic method known as the method of moments [26]. The KMC output, however, provides detailed information not available from deterministic models, such as the placement of comonomer (often functional) units in the chains across the molar mass distribution [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a modification on the kMC implementation to reduce simulation times was proposed. [50] Recently, it has been proposed that the polymerization of some vinyl monomers (methyl methacrylate (MMA), styrene (Sty) and n-butyl acrylate (nBuA) initiated by a redox reaction with N-hydroxyphthalimide (NHPI) and xanthone (XT) leads to the production of materials with controlled microstructures. [51] The polymerization scheme for such novel system is shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a modification on the kMC implementation to reduce simulation times was proposed. [ 50 ]…”
Section: Introductionmentioning
confidence: 99%